2014
DOI: 10.1159/000362096
|View full text |Cite
|
Sign up to set email alerts
|

Sphingoid Bases Inhibit Acid-Induced Demineralization of Hydroxyapatite

Abstract: Calcium hydroxyapatite (HAp), the main constituent of dental enamel, is inherently susceptible to the etching and dissolving action of acids, resulting in tooth decay such as dental caries and dental erosion. Since the prevalence of erosive wear is gradually increasing, there is urgent need for agents that protect the enamel against erosive attacks. In the present study we studied in vitro the anti-erosive effects of a number of sphingolipids and sphingoid bases, which form the backbone of sphingolipids. Pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 21 publications
0
49
0
Order By: Relevance
“…Solutions of PHS were prepared essentially as described earlier [Valentijn-Benz et al, 2015] to the indicated concentration in 20 mM Tris (Merck, Darmstadt, Germany) (pH = 6.8) supplemented with 0.1% Tween 20 (Tris-Tween; Sigma-Aldrich). Figure 1 shows the molecular structure of PHS.…”
Section: Phs and Inoculum Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solutions of PHS were prepared essentially as described earlier [Valentijn-Benz et al, 2015] to the indicated concentration in 20 mM Tris (Merck, Darmstadt, Germany) (pH = 6.8) supplemented with 0.1% Tween 20 (Tris-Tween; Sigma-Aldrich). Figure 1 shows the molecular structure of PHS.…”
Section: Phs and Inoculum Collectionmentioning
confidence: 99%
“…The determination of PHS adsorption to glass was performed essentially as described earlier [Valentijn-Benz et al, 2015]. Sterile glass cover slips (12 mm in diameter, 1 mm thick; Thermo Scientific, Braunschweig, Germany) were placed in the wells of 12-well cell culture plates (GreinerBio-One, Frickenhausen, Germany), to which 1.5 mL of a 200 μg/mL PHS solution was added, and incubated on a Heidolph Titramax 101 shaker (150 rpm, 30 min, 37 ° C).…”
Section: Phs Adsorption To Glassmentioning
confidence: 99%
“…Hence, the high density of positive charges on these aggregates would in effect produce a high avidity for negatively charged phosphate-rich surfaces e.g. HAp [Valentijn-Benz et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Each main group was then divided in three sub-groups (n = 5 per subgroup) based on the desensitising treatment as follows: PHS: 4-hydroxysphinganine (group A), DCP: brushite (group B), or PHS/ DCP: PHS + brushite (group C). A Tris-Tween/ethanol solution (5 mg/ml) of PHS was prepared as described by Valentijn-Benz et al [2015].…”
Section: Preparation Of Specimensmentioning
confidence: 99%
See 1 more Smart Citation